Effect of Helicobacter pylori eradication on anti-thrombotic dose aspirin-induced gastroduodenal mucosal injury - (:unkn) unknown (WILEY, 2004)
Background: Helicobacter pylori infection and non-steroidal anti-inflammatory drugs are two major causes of gastric injury but the effect of H. pylori eradication on the development of aspirin-induced gastric mucosal injury is unclear. The aim of the present study was to investigate the effect of Helicobacter pylori eradication on gastroduodenal mucosal injury induced by antithrombotic doses of aspirin. Methods: Patients who had been planned to start on medium-dose aspirin (300 mg) for any kind of indication were included in the study. All subjects underwent upper gastrointestinal endoscopy for determination of H. pylori status and Lanza score. The H. pylori-positive patients were randomized to receive either aspirin + eradication (omeprazole 20 mg b.i.d. and amoxicillin 500 mg q.i.d. for 2 weeks) or aspirin + placebo eradication. Endoscopic reassessment was done 4 months after the onset of aspirin or when symptoms developed. Results: Thirty-two patients (placebo group n = 16, H. pylori-eradicated group n = 16) completed the study and Lanza scores of both groups were similar before treatment. Lanza scores significantly increased in the placebo group (0.69 +/- 0.87 vs 2.25 +/- 1.3, P < 0.0001) and did not change in the H. pylori-eradicated group after aspirin treatment (0.43 +/- 0.72 vs 0.75 +/- 0.93, P > 0.05). Conclusion: Helicobacter pylori eradication may prevent medium-dose aspirin-induced gastroduodenal mucosal injury. (C) 2004 Blackwell Publishing Asia Pty Ltd.
Keywords: aspirin; gastroduodenal injury; Helicobacter pylori; DOUBLE-BLIND; CAMPYLOBACTER-PYLORI; INFECTION; NSAIDS; PLACEBO; DISEASE; ANGINA; ULCERS; TRIAL; RISK